LEXICAL CONSTRAINTS IN TRANSLATION AND LEARNING ENGLISH AS A FOREIGN LANGUAGE IN INDONESIA - Priyono Priyono (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
One of the main problems in the process of translating and learning English as a foreign language may be attributed to lexical constraints. Problems exist in both processes (translating and learning) because the two languages involved represent two different systems of expression. The differences in lexical structure between English and Indonesian are predicted to be the main cause of difficulties for EFL learners and translators. Using lexical conceptual structure (LCS), this study has collected data from authentic sources including English novels, brochures, textbooks, bulletins and newspapers. From this data we have identified five types of problems: These problems will be referred to as denominalized verbs or nouns surface as verbs, deadjectival verbs or adjectives surface as verbs, verb semantic structure, collocational combination, and transitive-intransitive alternation. The analysis of these cases has demonstrated that potential problems associated with each case are all lexically related. Therefore it will be argued in this paper that these five cases are part of the main causes for the problems faced by translators and EFL learners.